PENGARIH KOMPENSASIAN PADA KINERJA KEPEGAWAIAN DI PEMERINTAHAN KECAMATAN GOMO KAB. NISEL - David Putra Jaya Hulu (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
In the research, it can be seen that there is an influence of compensation on employee performance. In this implementation, there is a place where this is carried out in the Gomo sub-district government, regency. Nisel. This research uses a quantitative method which has an associative eel, which contains various calculations and ways of solving a research problem. The results of this research are that compensation really does affect employee performance. To improve employee performance, employee compensation should be more balanced with the tasks assigned. 2) To produce employee performance, employees must work better and not delay the work they have been assigned.